Parodia y desmitificación en la poesía de Luis Hernández - Mendoza-Canales, Ricardo (2009)
Despite of his desire for inscribing himself into a Modern (Romantic) poetic tradition, Luis Hernandez’ poetry reveals an inner tension as a result of fragmentation of postmodern subject. This essay studies the use of parody in Luis Hernandez’ poetry as a discursive strategy that plays a double dissemination: on the one hand, parody demystifies the standard conventions of his time about poetry and poetic language as a belle art and about the notion of author as the ultimate redoubt of signification. On the other hand, in Hernandez’ poetry, parody opens the field of meaning ISSN 0254-9239256 Lexis  Vol. XXXIII (2) 2009just for including intertextual and cultural features that dissolve, in poetic praxis, the division between high and mass culture.